2020
DOI: 10.1515/jpm-2020-0239
|View full text |Cite
|
Sign up to set email alerts
|

Academic clinical learning environment in obstetrics and gynecology during the COVID-19 pandemic: responses and lessons learned

Abstract: COVID-19 pandemic is changing profoundly the obstetrics and gynecology (OB/GYN) academic clinical learning environment in many different ways. Rapid developments affecting our learners, patients, faculty and staff require unprecedented collaboration and quick, deeply consequential readjustments, almost on a daily basis. We summarized here our experiences, opportunities, challenges and lessons learned and outline how to move forward. The COVID-19 pandemic taught us there is a clear need for collaboration in imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The data from our study reported the majority of our students do not encounter problems in accessing online class, evidence by majority have access to devices and scored above median score for satisfaction. This was similar to studies done among students in Hawaii (8) and Israel (9) where there was no problem in terms of technology. With the current generation who are more exposed to technology, this correlates to the finding where the majority (85.7%) feel that they have more opportunity to use the information they access on their own.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data from our study reported the majority of our students do not encounter problems in accessing online class, evidence by majority have access to devices and scored above median score for satisfaction. This was similar to studies done among students in Hawaii (8) and Israel (9) where there was no problem in terms of technology. With the current generation who are more exposed to technology, this correlates to the finding where the majority (85.7%) feel that they have more opportunity to use the information they access on their own.…”
Section: Discussionsupporting
confidence: 89%
“…This opportunity may be limited when they are attached to clinical areas when most of their learning time will be spent on observing or performing the procedures, thus limited time to reflect or to search for knowledge online. This finding was similar to the study done among medical students and residents of Hawaii medical schools who feel that the alteration provides them more opportunities to read, expand their knowledge and even complete their research projects (8).…”
Section: Barriersupporting
confidence: 86%
“…In the Spring of 2020, the coronavirus disease 2019 (COVID‐19) pandemic abruptly affected academic institutions and education programs in the United States and across the globe 1,2 . In‐person classroom instruction quickly pivoted to online synchronous and asynchronous platforms with the closure of university campuses.…”
Section: Introductionmentioning
confidence: 99%
“…In the Spring of 2020, the coronavirus disease 2019 (COVID-19) pandemic abruptly affected academic institutions and education programs in the United States and across the globe. 1,2 In-person classroom instruction quickly pivoted to online synchronous and asynchronous platforms with the closure of university campuses. Clinical experiences for health professional students were suspended from most facilities, including midwifery and women's health nurse practitioner (WHNP) education programs.…”
Section: Introductionmentioning
confidence: 99%